Optical properties of graphene in magnetic and electric fields - Lin, Chiun-Yan; Do, Thi-Nga; Huang, Yao-Kung; Lin, Ming-Fa (IOP Publishing, 2017)
This book provides a synthesis of up to date research on the optical properties of graphene, drawing from both experimental and theoretical research. The focus is primarily on multilayer graphenes with a focus on Landau-level spectra and the generalised tight-binding model. The interplay between external fields and the geometric configuration determines relationships between the components of wave functions in different sublattices. This leads to observation that the optical properties display a strong dependence on the stacking configuration and the number of layers. In general, this model can reasonably comprehend the quantization effect in arbitrarily stacked graphenes as well as other layered 2D materials such as MoS2 and silicene. Comparisons between theoretical and experimental work are drawn, as are the different graphene synthesis methods
"Version: 20171201"--Title page verso. - Includes bibliographical references
Keywords: Condensed matter physics (liquid state & solid state physics) / bicssc; SCIENCE / Physics / Condensed Matter / bisacsh; Graphene / Optical properties; Magnetic fields; Electric fields; Optische Eigenschaft; Magnetfeld; Graphen; Elektrisches Feld